Additions to knowledge of the biodiversity of benthic hydroids (Cnidaria: Hydrozoa) in the Balleny Islands (Antarctica) - CANTERO, ÁLVARO L. PEÑA (Zootaxa, 2021)
The Balleny Islands, an isolated archipelago located 240 km off the coast of Victoria Land (East Antarctica), are separated from the Antarctic continental shelf by waters more than 2000 m deep. The benthic hydroid fauna of these islands is little known, with only 25 species reported so far. The present study contributes to a better knowledge of the benthic hydrozoans inhabiting this archipelago by studying a small collection held at the National Institute of Water and Atmospheric Research Invertebrate Collection at Wellington, New Zealand. Sixteen species of benthic hydroids were found in the collection, belonging to nine families and 12 genera of Leptothecata. Kirchenpaueriidae and Oswaldella, with three species each, are the most speciose family and genus. Ten species represent new records for the region. The total number of benthic hydroid species known from the islands is raised to 34.